2020
DOI: 10.1080/14461242.2020.1851610
|View full text |Cite
|
Sign up to set email alerts
|

Not your unicorn: trans dating app users’ negotiations of personal safety and sexual health

Abstract: This article has been corrected with minor changes. These changes do not impact the academic content of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Furthermore, excerpts illustrated a conflict between adolescents' desire to be genuine online and concerns about the acceptability of their gender identity, echoing findings among TGD adults (Albury et al, 2020;Fernandez & Birnholtz, 2019). Compared with previous findings that TGD adults shared their identity as a pragmatic strategy to filter out incompatible partners (Albury et al, 2020), TGD teens' desire to disclose their identity online may also reflect a sense of pride in their TGD identity, as reflected in the "honesty and genuineness" code. The tension between TGD teens' desire for and fears of identity disclosure online may feel more acute given their developmental stage.…”
Section: Tgd Adolescents' Questions About Online Relationship Seekingmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, excerpts illustrated a conflict between adolescents' desire to be genuine online and concerns about the acceptability of their gender identity, echoing findings among TGD adults (Albury et al, 2020;Fernandez & Birnholtz, 2019). Compared with previous findings that TGD adults shared their identity as a pragmatic strategy to filter out incompatible partners (Albury et al, 2020), TGD teens' desire to disclose their identity online may also reflect a sense of pride in their TGD identity, as reflected in the "honesty and genuineness" code. The tension between TGD teens' desire for and fears of identity disclosure online may feel more acute given their developmental stage.…”
Section: Tgd Adolescents' Questions About Online Relationship Seekingmentioning
confidence: 77%
“…These concerns may reflect the victimization experienced by TGD individuals (Gordon & Meyer, 2007;Johns et al, 2019) and transphobia within the SGM community (Araya et al, 2021). Furthermore, excerpts illustrated a conflict between adolescents' desire to be genuine online and concerns about the acceptability of their gender identity, echoing findings among TGD adults (Albury et al, 2020;Fernandez & Birnholtz, 2019). Compared with previous findings that TGD adults shared their identity as a pragmatic strategy to filter out incompatible partners (Albury et al, 2020), TGD teens' desire to disclose their identity online may also reflect a sense of pride in their TGD identity, as reflected in the "honesty and genuineness" code.…”
Section: Tgd Adolescents' Questions About Online Relationship Seekingmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, this study had too few gender-nonconforming and transgender respondents to include them in analyses. Prior research has found that these individuals are at an increased risk of sexual victimization and that this risk extends to the use of LBRTDAs (e.g., Albury et al, 2020). Future scholarship, including qualitative work, should more thoroughly explore the experiences of sexual minorities with respect to LBRTDA use and specific forms of cybervictimization.…”
Section: Discussionmentioning
confidence: 99%
“…Future scholarship, including qualitative work, should more thoroughly explore the experiences of sexual minorities with respect to LBRTDA use and specific forms of cybervictimization. Indeed, victimization experiences may have larger implications for these individuals when compared with their cisgender, heterosexual counterparts (Albury et al, 2020; Steinfeld, 2020). Approaching future LBRTDA victimization research through an intersectional lens allows for the critical and necessary examination of the nuances and linkages across different groups of users and their individual experiences.…”
Section: Discussionmentioning
confidence: 99%